Abdominal scar endometriosis-a dilemma in diagnosis - Singh, Sonu; Shrivastav, Ayushi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Abdominal scar endometriosis is a rare disease with an incidence of 0.03-0.15%. Its diagnosis is often confused with other conditions like hematoma, granuloma, keloid, incisional hernia and vascular malformation. We are reporting two cases of abdominal scar endometriosis with some diagnostic dilemmas. In first case it was previously reported as stitch granuloma due to atypical clinical presentation. In second case CT scan reported it to be a likely neoplastic lesion. In both the cases, wide excision of the lesion with a safe margin was planned and was further confirmed by histopathology. On follow up both patients are currently asymptomatic.